LOCAL SEEDS OF THE IDEA OF EDUCATION ARE LOOKING FOR FERTILE GROUND TO GROW - Akpınar, Burhan (İstanbul İlim ve Kültür Vakfı, 2025)
The purpose of this compilation is to discuss current opportunities and obstacles to raise awareness about efforts to establish a local and national education philosophy and model in the Turkish context. The data sources for this study, conducted using a screening model within the framework of qualitative research, are relevant written and digital documents. These documents, selected in accordance with qualitative research methodology, were analyzed using document analysis. This analysis, in line with the study's purpose, was conducted through the stages of reading, describing, interpreting, and drawing conclusions. The study's conclusions can be summarized as follows: While the civilizational crisis experienced by our nation, our Ummah, and humanity today stems from many causes, education (education) and culture are among the most common suspects. For the civilizational crisis we are experiencing is not only due to humanity's corrupted nature and conscience, but also to its intellectual erosion. This intellectual erosion is the result of two centuries of education poisoned by modernism, positivism, and materialism. Education, based on the purely irreligious philosophies and paradigms of a god-hating Western civilization, has not only severed the bond between God, humanity, and nature, but has also corrupted human purity, reducing reason to the eye and blinding minds to spirituality. While this nature of education may not pose a problem for Western civilization, it is the cause of the limbo state experienced by Islamic societies, which oscillate between spiritual belief and material prosperity. While there are other reasons, the Turkish Education System's constant search for models can be interpreted as an effort to escape such a limbo state. However, these efforts, undertaken using Western methods, cannot go beyond an "incomplete restoration," perhaps due to the incompatibility between the method and the true purpose. In recent years, the courageous efforts of national and local strides in the defense industry have attracted attention, as have efforts to shift the course of education toward a national direction. However, for these efforts to yield a truly national education, both in theory and practice, requires, above all, indigenous philosophies, ideas, models, curricula, principles, and practices. This is possible primarily by producing words and concepts, the indigenous materials of the educational edifice, or by extracting them from history and reviving them in the 21st century. At this point, while numerous educational philosophies, ideas, models, or curricula, many of which are still incubating in our country and throughout the Islamic world, offer hope, the barrier of mocking, disregarding, and most importantly, distrusting them, perhaps due to admiration for the West, dampens the enthusiasm of the minds that produce them. Ultimately, the indigenous seeds of the idea of education are seeking fertile ground to flourish. Building this fertile ground depends on the trust, will, and dedication displayed by official bodies and/or foundations, associations, and NGOs that will bring together and support the intentions, efforts, and ideas of our wise thinkers for specific purposes. Otherwise, we will continue to relegate education, a process of mind-building, to imported philosophies and ideas, acquiesce to reproach, and perpetuate the oddity of singing local folk songs with someone else's instrument. The obstacle to this is primarily ourselves, and therefore, the message to us should be, "Get out of your way!"

Derleme niteliğindeki bu çalışmanın amacı, Türkiye bağlamında yerli ve millî maarif felsefesi ve modeli ihdas etme çabalarına dair farkındalık oluşturmak maksadıyla, mevcut fırsatlar ile engelleri tartışmaktır. Nitel araştırmalar çerçevesinde yer alan tarama modelinde yürütülen çalışmanın veri kaynakları, ilgili yazılı ve dijital belgelerdir. Nitel araştırma metodolojisine uygun olarak seçilen bu belgeler, doküman analizi tekniği kullanılarak çözümlenmiştir. Çalışma amacı doğrultusundaki bu çözümleme, ilgili belgelerin okunması, betimlenmesi, yorumlanması ve sonuç çıkarma aşamaları şeklinde gerçekleştirilmiştir. Çalışmada ulaşılan sonuçlar şu şekilde özetlenebilir: Bugün, milletimiz, ümmetimiz ve insanlığın yaşadığı medeniyet krizi birçok nedene bağlı olsa da, eğitim (maarif) ve kültür olağan şüpheliler arasında başı çekmektedir. Zira yaşadığımız medeniyet krizinde, beşerin bozulan fıtrat ve vicdanı kadar, zihinsel erozyonunun da payı büyüktür. Bu zihinsel aşınma ise, iki asırdır modernizm, pozitivizm ve materyalizmle zehirlenen maarifin neticesidir. Tanrıya küs Batı uygarlığının, katıksız din dışı felsefe ve paradigmalarına dayalı maarif, Allah-İnsan-Tabiat arasındaki bağı koparmakla kalmamış, insanın saflığını da bozarak, aklı göze indirmiş ve zihinleri maneviyata karşı kör etmiştir. Bu mahiyetteki maarif, Batı uygarlığı için mesele teşkil etmese de, manevi inanç ile maddi ikbal spektrumunda salınan İslam toplumları için yaşanmakta olan araf halinin sebebidir. Başka nedenleri olsa da, Türk Eğitim Sisteminin sürekli model arayışları böylesi bir araf halinden kurtulma çabası olarak okunabilir. Ancak Batı’nın usulleriyle girişilen bu çabalar, usul ile asıl maksat arasındaki uyumsuzluktan olsa gerek, “eksik restorasyondan ” öteye gidememektedir. Son yıllarda savunma sanayinde kat edilen milli ve yerli adımların cesaretiyle, eğitimde rotayı mili yöne doğru çevirme gayretleri dikkat çekmektedir. Ancak bu çabaların, teori ve uygulamasıyla birlikte topyekun milli bir maarifi netice vermesi, her şeyden önce yerli felsefe, fikir, model, müfredat, ilke ve tatbikatları gerektirir. Bu ise öncelikle maarif binasının yerli malzemeleri olan kelime ve kavramları üretmek veya tarihten istihraç ederek, 21. yüzyıl kabında diriltilmekle mümkündür. Bu noktada, gerek ülkemizde ve gerekse İslam coğrafyasında birçoğu zihinlerde kuluçka merhalesinde olan çok sayıda maarif felsefesi, fikri, modeli veya müfredatı umut verse de, Batı hayranlığından olsa gerek, bunları istihza etme, dikkate almama ve en önemlisi de bunlara güvenmeme gibi bariyerler, bunları mahsul veren zihinlerin hevesini kırmaktadır. Son tahlilde, maarif fikrine dair yerli tohumlar yeşermek için mümbit zemin arıyor. Bu mümbit zeminin inşası ise hüşyar düşünürlerimizin niyet, çaba ve fikirlerini belirli amaçlar doğrultusunda bir araya getirip, destekleyecek resmi ve/veya vakıflar, dernekler ya da STK tarafından ortaya konulacak itimat, irade ve himmet adımlarına bağlıdır. Yoksa zihin inşa ameliyesi olan maarifi, ithal felsefe ve fikirlere havale edip, serzenişe razı olmaya devam edeceğiz ve başkasının sazıyla yerli türkü söyleme garabetini sürdüreceğiz. Buna engel ise öncelikle biziz, dolayısıyla bu bize söylenecek söz de, “çekilin önünüzden!” olmalıdır.
MAARİF FİKRİNE DAİR YERLİ TOHUMLAR YEŞERMEK İÇİN MÜNBİT ZEMİN ARIYOR
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)